Pengaruh model project based learning (PjBL) terhadap dimensi bernalar kritis P3 pada pembelajaran IPA di siswa Kelas IV sekolah dasar - Alifia Salsabila Ramadhani; Peduk Rintayati; Chumdari Chumdari (Universitas Sebelas Maret, 2023)
Many schools have not successfully empowered students’ critical thinking skills in science subject learning due to inappropriate learning models. This article aims to describe the impact of the project-based learning (PjBL) model on the critical reasoning skill dimension of P3. This quantitative research method is using quasi-experimental with a Non-equivalent Control Group Design type using a pretest-posttest on the sample class. The selection of the sample class used a multistage random sampling technique. The sample used 73 students, and it consist of 26 experimental class students, 22 control class students, and 26 test class students. This study data were analyzed using paired sample t-test and independent sample ttest. The data had previously met the prerequisite test analysis. The findings indicated a significant positive impact on the benefit of PjBL models toward the critical thinking dimension (on Profil Pelajar Pancasila/ P3) of 4 th -grade elementary school students.